Effect of material properties on ballistic energy absorption of woven fabrics subjected to different levels of inter-yarn friction. (15th June 2021) - Ingle, Sagar; Yerramalli, Chandra Sekher; Guha, Anirban; Mishra, Sushil
Highlights: The ballistic energy absorption capacity of materials with similar toughness values are not always the same. Optimum COF value beyond which there is drop in ballistic performance of fabric is function of yarn material properties. The optimum COF values are lower for materials with low modulus and high failure strain as compared to materials with high modulus and low failure strain. The ballistic energy absorption capacity of every material may not benefit with an excessive increase in COF and in fact may show an opposite effect. Abstract: Inter-yarn friction plays a significant role in ballistic energy absorption of woven fabrics. In the past decade, a few studies have been reported on the effect of inter-yarn friction on ballistic energy absorption. It has been reported that ballistic energy absorption of a woven fabric increases until an optimum value of the coefficient of friction 1 (COF) and decreases beyond that. However, a fundamental understanding of how yarn material properties affect this optimum friction value is still elusive. The effect of yarn material properties on different modes of ballistic energy absorption, when subjected to different inter-yarn friction level, is also not understood. In order to address this lacuna, this work presents a detailed numerical analysis of woven fabrics with different material properties but constant toughness subjected to different inter-yarn friction using the finite element framework. The results show that for materials with a low value of longitudinal modulus and higher value of failure strain, the threshold friction level is of lesser magnitude than in materials with a high value of longitudinal modulus and lower failure strain value. An explanation of this phenomenon has also been attempted based on a study of longitudinal stress wave velocity in woven fabrics with different levels of inter-yarn friction. It has also been found that an increase in the inter-yarn friction level increases the ballistic energy absorption in fabric strain energy mode while it decreases the energy absorption in fabric kinetic energy mode up to the threshold friction value. The results are expected to be a guide to choose woven fabrics while attempting to improve their ballistic performance by impregnating them with shear thickening fluids 2 (STF).